2003
DOI: 10.1002/jso.10198
|View full text |Cite
|
Sign up to set email alerts
|

Association between extent of axillary lymph node dissection and patient, tumor, surgeon, and hospital factors in patients with early breast cancer

Abstract: Even though the number of lymph nodes found in the pathologic specimen can be influenced by factors other than surgical technique (e.g., number of nodes present, specimen handling, and pathologic examination), this study shows significant variation of this variable and an association with several patient and surgeon/hospital factors. This variation and the association with survival warrant further study and effort at greater consistency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 35 publications
4
18
3
Order By: Relevance
“…The expertise of the individual surgeon as well as pathologist on the LNY was considered a strong predictor for the LNY [20,22,23]. However, in our study cohort multivariate analyses could not detect any significant influence of lymph node retrieval by the involved specialists as well as specific interactions between them.…”
Section: Discussioncontrasting
confidence: 54%
“…The expertise of the individual surgeon as well as pathologist on the LNY was considered a strong predictor for the LNY [20,22,23]. However, in our study cohort multivariate analyses could not detect any significant influence of lymph node retrieval by the involved specialists as well as specific interactions between them.…”
Section: Discussioncontrasting
confidence: 54%
“…How these various factors impact the LN yields for SBA is not known but the same factors are likely relevant, as studies in other tumor types have noted the importance of these same factors. 35, 36 In a prior SEER registry study, assessment of ≥8 LNs was identified to be the optimal cut-point for discriminating differences in cancer-specific survival. 21 We therefore utilized this cut-point in the present analysis as a means to minimize the potential effects of stage-migration.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that surgeon training and academic affiliation also influence the quality and degree of axillary node dissection. 23, 24 …”
Section: Discussionmentioning
confidence: 99%